Impact-resistant flame-retardant PC alloy with melt flowability and preparation method of impact-resistant flame-retardant PC alloy
By combining core-shell flame retardants and toughening agents, the technical challenges of balancing flame retardancy, flowability, and impact resistance in PC/ABS alloys have been solved. This approach achieves high-efficiency flame retardancy and excellent flowability with low additive levels, while also improving impact resistance, making it suitable for complex molded products.
Patent Information
- Application Number
- CN202511321558.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2025-12-02
AI Technical Summary
Existing PC/ABS alloys face a difficult technical challenge in balancing high flame retardancy, good flowability, and strong impact resistance. Traditional flame retardants can affect the material's flowability and impact resistance, while the addition of halogen-free flame retardants can increase melt viscosity and brittleness.
The core-shell flame retardant uses a combination of nano-SiO2 loaded with sulfonate, low molecular weight PC and epoxy polysiloxane to form a chemical bonding interface, which enhances the dispersion stability of the flame retardant and forms a multi-layer physical barrier during combustion, thus synergistically improving the flame retardant efficiency. At the same time, the compounding of toughening agents improves the interfacial bonding force and impact resistance.
Achieving UL94 V0 flame retardancy at low addition levels improves material flowability and impact resistance, avoids the negative impact of traditional flame retardants on material performance, and meets complex molding requirements.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of PC alloys, and in particular to an impact-resistant and flame-retardant PC alloy with melt flowability and its preparation method. Background Technology
[0002] Polycarbonate (PC), as a high-performance engineering plastic, is widely used in electronics, automotive manufacturing, and construction due to its excellent impact strength, light transmittance, heat resistance, and electrical insulation. However, PC itself has shortcomings such as high melt viscosity and poor flowability. Especially when molding large or complex structural products, the melt is difficult to fill the mold cavity quickly and uniformly, which can easily lead to defects such as material shortage and weld lines, limiting its application in a wider range of scenarios.
[0003] To improve the processing performance of PC and balance its overall properties, the most common modification method in the industry is to blend PC with acrylonitrile-butadiene-styrene copolymer (ABS) to form PC / ABS alloy. This retains the impact resistance and heat resistance of PC while taking advantage of the good flowability and processability of ABS, thus broadening the range of molding applications for the material and making it the mainstream choice for electronic and electrical housings, automotive interior parts, and other components.
[0004] However, in practical applications of PC / ABS alloys, there is always an irreconcilable relationship between flame retardancy, flowability, and impact resistance: if the focus is on improving flowability, such as increasing the proportion of ABS or adding flow promoters, although the molding effect can be improved, it may destroy the continuous phase structure of PC, leading to a decrease in the material's impact resistance. At the same time, some flow promoters may also weaken the stability of the flame retardant system. To meet flame retardant requirements, adding bromine-based flame retardants is highly efficient, but it will release toxic gases and may reduce the material's toughness. Halogen-free flame retardants often require high addition amounts, which not only increases melt viscosity and worsens flowability, but also makes the material brittle due to the introduction of a large amount of inorganic components, further sacrificing impact resistance. If you want to enhance impact resistance, introducing toughening agents is a common method, but most toughening agents (such as rubber-based ones) will reduce the material's rigidity and heat resistance, and may even lead to a decrease in the flame retardant effect. At the same time, excessive toughening agents may also increase melt viscosity, which in turn affects flowability.
[0005] Therefore, the development of PC / ABS alloys that balance high flame retardancy, good flowability, and strong impact resistance faces enormous challenges and has become a core technical problem that the industry urgently needs to overcome.
[0006] The information disclosed in this background section is intended only to enhance the understanding of the overall background of the present invention and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention provides an impact-resistant and flame-retardant PC alloy with melt flowability and its preparation method, overcoming the severe negative impact of existing flame retardants on the mechanical and processing properties of PC / ABS alloys, and enabling the material to achieve a balanced optimization of various properties while meeting the UL94 V0 rating.
[0008] The first objective of this invention is to provide an impact-resistant and flame-retardant PC alloy with melt flowability, comprising the following components by mass parts:
[0009] 60-70 parts of PC resin;
[0010] 30-40 parts of ABS resin;
[0011] 6-10 parts of core-shell flame retardant;
[0012] 5-8 parts toughening agent;
[0013] Compatibilizer 0.5–1.0 parts;
[0014] Antioxidant 0.3-0.5 parts;
[0015] Other adjuvants: 1.0–1.5 parts;
[0016] The core-shell flame retardant consists of nano-SiO2 loaded with sulfonate, low molecular weight PC, and epoxy polysiloxane from the inside out. The weight-average molecular weight of the low molecular weight PC is 5000-8000, and the epoxy value of the epoxy polysiloxane is 0.3-0.5 eq / 100g.
[0017] The toughening agent is prepared by mixing organosilicon toughening agent, MBS and hydrogenated SBS in a mass ratio of 2-3:3-4:1-2.
[0018] The core-shell flame retardant of this invention uses an epoxy-based polysiloxane shell. The epoxy groups of the shell react with the terminal hydroxyl groups of PC and the acrylonitrile groups of ABS to form a chemical bonding interface, which not only enhances the dispersion stability of the flame retardant, but also relieves impact stress by utilizing the flexibility of the siloxane chain segments. The melt viscosity of the low molecular weight PC in the middle layer is much lower than that of the base PC. During preparation, it can melt quickly and uniformly coat the core, forming a dense middle layer with controllable thickness, avoiding uneven coating. Moreover, its chemical structure is similar to that of the base PC. The short chains can penetrate into the intermolecular gaps of the base PC and form multi-point chain segment entanglement by van der Waals forces, which significantly reduces interfacial tension and reduces agglomeration. In addition, the thermal decomposition temperature of the low molecular weight PC is slightly lower. During combustion, it decomposes preferentially to form a molten coating layer, which is superimposed with the char-forming effect of the nano-SiO2 in the core to delay the thermal decomposition of the base. The sulfonate in the core releases fluorine-containing gas to capture free radicals, and the nano-SiO2 promotes char formation through surface hydroxyl groups to form a physical barrier. The two work together to improve the flame retardant efficiency.
[0019] More specifically, in the initial stage of combustion when the PC alloy obtained in this way is ignited on the material surface, the outer epoxy-based polysiloxane preferentially acts. At this time, the silicon-oxygen segments (-Si-O-) in the epoxy-based polysiloxane undergo oxidative cross-linking first, forming a dense SiO2-based ceramic film covering the material surface. This film acts as a physical barrier, directly blocking the contact between oxygen and the surface flame, while reflecting heat to delay the heating of the internal material, thus buying time for the core flame-retardant components to react. The chemical bond between the epoxy groups of the outer shell and the matrix interface remains stable at this stage, preventing the flame retardant from detaching due to surface melting and improving the sustainability of the subsequent flame-retardant effect. As combustion progresses, heat is transferred to the interior of the material, and the temperature rises to 350-450℃, which is the main decomposition range of PC / ABS. The low molecular weight PC in the middle layer, due to its short molecular chain, has slightly lower thermal stability than the matrix PC and preferentially decomposes, releasing inert substances such as phenols and CO2. The flammable gas dilutes the concentration of combustible gas in the combustion zone; the fluorine-containing free radicals generated by the decomposition of sulfonates released from the core rapidly capture H· and OH· in the combustion reaction, while the decomposition gases of low molecular weight PC further reduce the flame temperature. The two work together to inhibit the gas-phase combustion chain reaction; the compatibility between the intermediate layer and the PC matrix ensures that the core flame retardant is always evenly distributed in the decomposition area during heat transfer, avoiding the formation of combustion breakthroughs due to insufficient flame retardant components in some areas; when the temperature exceeds 450℃, the material enters the deep degradation stage. At this time, the surface hydroxyl groups of nano-SiO2 loaded with sulfonates in the core combine with the aromatic compounds generated by the decomposition of PC, catalyzing the formation of a more stable graphitized carbon layer. The nanoscale structure allows it to be evenly filled in the pores of the carbon layer, improving the carbon layer density; the rigid structure of nano-SiO2 can also enhance the molten viscosity of the material, reduce dripping, and together with the previously formed siloxane ceramic layer, form a physical barrier.
[0020] In the toughening system, the silicone toughening agent undergoes ring-opening reactions with the terminal hydroxyl groups of PC and the acrylonitrile groups of ABS through epoxy groups, forming a bridge in the matrix and strengthening the overall interfacial bonding. MBS absorbs room-temperature impact energy with the rubber phase as the core, and the shell layer improves the compatibility with ABS and the dispersion uniformity. Hydrogenated SBS maintains elasticity at low temperatures due to its saturated structure, compensating for the low-temperature toughening shortcomings of MBS. The three are compounded in a ratio of 2-3:3-4:1-2 to construct a full-temperature elastic network. The compatibilizer eliminates phase separation between PC and ABS through polar group reactions, the antioxidant compound inhibits thermal oxidative degradation, and other additives reduce melt viscosity through lubrication. Ultimately, a UL94 V0 flame retardant rating is achieved with low flame retardant addition, adapting to the fluidity of complex molding and providing stable impact resistance across the entire temperature range, thus resolving the performance conflicts of traditional systems.
[0021] As a preferred embodiment of the present invention, the weight-average molecular weight of the PC resin is 20,000 to 25,000, and the melt index at 300°C / 1.2 kg is 8 to 15 g / 10 min.
[0022] More specifically, the PC molecular chain length within the aforementioned molecular weight range is moderate, providing sufficient intermolecular entanglement to maintain mechanical properties such as tensile strength and flexural modulus, avoiding insufficient rigidity due to excessively low molecular weight, and preventing a sharp increase in melt viscosity due to excessively long chains. In this invention, PC resin provides skeletal support, and ABS reduces friction between PC chain segments through molecular chain interpenetration. Together, they enable the alloy melt to quickly fill thin-walled molds during injection molding without causing excessive shrinkage of the product due to excessive fluidity.
[0023] As a preferred embodiment of the present invention, the acrylonitrile content in the ABS resin is 22-25%, the butadiene content is ≤28%, and the melt index at 220℃ / 10kg is 15-30g / 10min.
[0024] More specifically, due to its strong polarity, the acrylonitrile unit can form dipole-dipole interactions with the carbonate groups of PC. A content of 22-25% is sufficient to suppress phase separation without increasing the brittleness of the material. The butadiene rubber phase, as an elastic dispersed phase, with a content of ≤28%, can provide a certain toughness at room temperature while avoiding the destruction of the continuous phase structure of PC due to excessive rubber phase. The melt index complements the fluidity of PC and can be interspersed between PC chain segments to reduce the friction in the melt. This allows the overall fluidity of the alloy to meet the molding requirements of complex products, while avoiding flash defects caused by the excessive fluidity of ABS during molding.
[0025] As a preferred embodiment of the present invention, in the core-shell flame retardant, the mass ratio of nano-SiO2 loaded with sulfonate, low molecular weight PC, and epoxy polysiloxane is 3-5:6-8:8-10.
[0026] The nano-SiO2 has an average particle size of 50–100 nm, a surface hydroxyl content of ≥1.5 mmol / g, and a sulfonate loading of 5–10 wt% on the nano-SiO2.
[0027] More specifically, the average particle size of nano-SiO2 is 50–100 nm. This size range provides a large specific surface area to load more sulfonates, thereby improving the gas-phase flame retardant efficiency, while avoiding the tendency of agglomeration caused by excessively small particle size. The surface hydroxyl content is ≥1.5 mmol / g, which can bind with the terminal hydroxyl groups of low molecular weight PC through hydrogen bonds, thereby strengthening the stability of the intermediate layer coating and reducing the risk of delamination during processing. The sulfonate loading is 5–10 wt%, which improves the gas-phase flame retardant effect and prevents sulfonates from falling off the surface of nano-SiO2, maintaining stable flame retardant efficiency.
[0028] In the core-shell structure, the outer shell has a relatively high proportion of epoxy-based polysiloxane, which provides sufficient reaction sites with the matrix. At the same time, the proportion of low molecular weight PC in the middle layer can improve the compatibility with the PC matrix and avoid interface defects caused by direct contact between the inorganic phase of the core and the matrix.
[0029] Preferably, the sulfonate is one or more of potassium perfluorobutyl sulfonate, potassium perfluorohexyl sulfonate, and sodium perfluorooctyl sulfonate;
[0030] The aforementioned perfluoroalkyl sulfonates contain highly stable CF bonds, which can directionally decompose at high temperatures to release fluorine-containing gases such as HF. This not only dilutes the oxygen and combustible volatile components in the combustion zone but also forms a dense gas barrier to isolate the combustion interface. Simultaneously, the highly reactive fluorine-containing free radicals generated during decomposition can efficiently capture key active free radicals such as H· and OH· in the combustion chain reaction, cutting off the core driving force for the continuous spread of flames. The carbon chain length of the aforementioned perfluoroalkyl sulfonates is moderate, and the short-chain structure avoids the steric hindrance problem of long-chain perfluorinated compounds. It can achieve a uniform loading of 5-10 wt% on the surface of nano-SiO2 and is not prone to agglomeration due to excessively strong intermolecular forces. Potassium and sodium ions, as cations, can reduce the activation energy of cross-linking aromatic compounds generated by PC decomposition into char at high temperatures through charge interaction, promoting char layer formation. They also synergistically enhance the density of the char layer with the hydroxyl groups on the surface of nano-SiO2, strengthening the flame retardancy of the condensed phase.
[0031] As a preferred embodiment of the present invention, the method for preparing the core-shell flame retardant includes:
[0032] S1. Vacuum-dried nano-SiO2 is prepared for later use; low molecular weight PC is passed through a 200-mesh sieve to remove agglomerated particles and then prepared for later use.
[0033] S2. Nano-SiO2 was ultrasonically dispersed in acetone, sulfonate was added and stirred at 25-35℃ for 1.5-2.5 h, filtered, washed and vacuum dried to obtain nano-SiO2 cores loaded with sulfonate.
[0034] S3 preheats the sulfonate-loaded nano-SiO2 cores at 70-90℃ and 400-600r / min for 4-6min, adds low molecular weight PC and heats to 110-130℃, stirs at 700-900r / min for 25-35min, cools and pulverizes through a 100-mesh sieve to obtain composite particles.
[0035] S4 disperses the composite particles in toluene, adds epoxy-based polysiloxane and diisopropylbenzene peroxide, reacts at 100-120℃ for 1.5-2.5 h under nitrogen protection, washes and vacuum dries to obtain the core-shell flame retardant.
[0036] As a preferred method, the preparation method of the core-shell flame retardant includes:
[0037] S1. Dry the nano-SiO2 particles under vacuum at 110-130℃ for 3-5 hours for later use; remove agglomerated particles by passing the low molecular weight PC powder through a 180-220 mesh sieve for later use.
[0038] S2. Disperse 3-5 parts of dried nano-SiO2 particles in 90-110 parts of acetone, and ultrasonically disperse at 250-350W for 25-35 min to form a uniform suspension; add 0.15-0.5 parts of sulfonate, controlling the sulfonate loading at 5-10 wt%, and stir at 25-35℃ for 1.5-2.5 h to allow the sulfonate to be adsorbed onto the surface of the nano-SiO2 by electrostatic attraction, avoiding uneven local loading; vacuum filter, wash with acetone 2-4 times to remove free sulfonate, and vacuum dry at 50-70℃ for 5-7 h to obtain sulfonate-loaded nano-SiO2 cores;
[0039] S3. Add 3-5 parts of sulfonate-loaded nano-SiO2 cores to a high-speed mixer and preheat at 70-90℃ and 400-600 r / min for 4-6 min to activate the core surface; slowly add 6-8 parts of low molecular weight PC powder, heat to 110-130℃ (above the melting point of low molecular weight PC), and stir at 700-900 r / min for 25-35 min. Utilize the melt flowability of low molecular weight PC to coat the surface of the sulfonate-loaded nano-SiO2 cores, forming a uniform intermediate layer to avoid localized exposure due to insufficient stirring; cool to room temperature, pulverize, and pass through a 100-mesh sieve to obtain composite particles;
[0040] S4. Disperse 10 parts of composite particles in 40-60 parts of toluene, add 8-10 parts of epoxy-based polysiloxane and 0.15-0.25 parts of dicumyl peroxide, and heat to 100-120℃ under nitrogen protection; stir the reaction for 1.5-2.5 hours to achieve the grafting rate target. During the process, dicumyl peroxide initiates the free radical grafting reaction between epoxy-based polysiloxane and the intermediate PC layer, allowing epoxy-based polysiloxane to be grafted onto the benzene ring or end group of low molecular weight PC through free radicals, forming a chemically bonded outer shell layer. Nitrogen protection is used during this process to prevent oxidation side reactions. After cooling, filter, wash 1-3 times with a toluene-ethanol mixture, and vacuum dry at 70-90℃ for 7-9 hours to obtain the final core-shell flame retardant.
[0041] The above preparation method enables the three-layer structure to be tightly bound together by chemical bonds or strong interactions, avoiding interlayer delamination that occurs during processing in traditional physically mixed flame retardants, and improving the stability of flame retardant performance.
[0042] As a preferred embodiment of the present invention, the toughening agent is an epoxy polysiloxane, the rubber phase content of MBS is 50-60 wt%, and the average particle size is 0.1-0.3 μm; the hydrogenation degree of hydrogenated SBS is ≥95%, the styrene segment content is 30-40 wt%, and the ethylene-butene segment content is 60-70 wt%.
[0043] More specifically, the MBS rubber phase can fully absorb energy through deformation upon impact. The average particle size of 0.1–0.3 μm allows MBS to be uniformly dispersed into micro-regions, inducing crazes rather than cracks in the matrix through stress concentration. Hydrogenated SBS with a hydrogenation degree of ≥95% eliminates the double bonds in the butadiene segments, avoiding loss of elasticity due to molecular chain freezing at low temperatures. The 30–40 wt% styrene segment has good compatibility with the SAN phase of ABS, reducing interfacial tension. The 60–70 wt% ethylene-butene segment provides low-temperature flexibility. When epoxy-based polysiloxanes are compounded with both, the reaction between the epoxy groups and the matrix enhances interfacial bonding. The low glass transition temperature (Tg) of the siloxane segments further broadens the toughening temperature range and reduces notched impact strength fluctuations.
[0044] As a preferred embodiment of the present invention, the compatibilizer is one or a mixture of two or more of ABS-g-MAH, SAN-g-MAH and SAN-g-GMA;
[0045] More specifically, in the molecular structure of ABS-g-MAH, the ABS backbone has excellent compatibility with the SAN phase and rubber phase of the matrix ABS, and can be embedded into the ABS phase through molecular chain entanglement; while the grafted maleic anhydride group (MAH) has strong polarity and can undergo esterification reaction with the terminal hydroxyl groups of PC molecular chain to form a chemically bonded PC-ABS-g-MAH-ABS interface structure, which effectively reduces the interfacial tension between PC and ABS.
[0046] The SAN backbone of SAN-g-MAH is completely compatible with the SAN phase of ABS. The grafted maleic anhydride groups can also react with the hydroxyl groups of PC. Its mechanism of action is similar to that of ABS-g-MAH. However, because it does not contain a rubber phase, it is easier to form a uniformly distributed molecular bridge at the interface between the PC and the SAN phase of ABS. When compounded with ABS-g-MAH, the two focus on combining with the rubber phase of ABS and SAN respectively, forming an all-round interface anchoring and further reducing phase separation.
[0047] The epoxy groups of GMA in SAN-g-GMA can undergo ring-opening reactions with the terminal hydroxyl groups of PC. The epoxy groups break and combine with the hydroxyl groups to form ether bonds. The reactivity is higher than that of maleic anhydride, and interfacial bonding can be achieved at lower processing temperatures. At the same time, the compatibility of the SAN backbone with the SAN phase of ABS allows it to be uniformly dispersed in the interfacial region. When compounded with the first two compatibilizers, the epoxy groups and maleic anhydride groups combine with PC from different reaction sites to form a multi-point cross-linked interface, which significantly improves the interfacial layer strength.
[0048] As a preferred embodiment of the present invention, the antioxidant is a compound of hindered phenolic antioxidant and phosphite antioxidant, with a mass ratio of 1:1.
[0049] Other additives include silicone flow agents and lubricants, with a mass ratio of 1 to 2:1.
[0050] The lubricant is ethylene bis-stearamide or pentaerythritol stearate;
[0051] More specifically, hindered phenolic antioxidants, such as antioxidant 1010, terminate oxidation chain reactions by capturing free radicals; phosphites, such as antioxidant 168, decompose hydroperoxides. When the two are combined in a 1:1 ratio, the hindered phenols first eliminate existing active free radicals and break the current oxidation chain, while the phosphites then decompose hydroperoxides, preventing the initiation of new oxidation chains. This forms a dual protection that terminates existing oxidation and blocks the initiation of new oxidation, resulting in higher antioxidant efficiency than a single antioxidant.
[0052] Among other additives, silicone flow agents improve melt flowability by reducing the intermolecular friction coefficient, while pentaerythritol stearate or ethylene bis-stearamide form a lubricating film on the material surface, reducing friction with the mold. A 1 to 2:1 ratio balances the silicone as an internal lubricant with the lubricant as an external lubricant, preventing the migration of the release agent due to excessive external lubrication.
[0053] A second objective of this invention is to provide a method for preparing the above-mentioned impact-resistant and flame-retardant PC alloy with melt flowability, comprising the following steps:
[0054] (1) Dry the PC resin at 120-130℃ for 4-6 hours and the ABS resin at 80-90℃ for 3-4 hours; more specifically, drying the PC resin at 120-130℃ for 4-6 hours can remove moisture and prevent hydrolysis and chain breakage during processing; drying the ABS resin at 80-90℃ for 3-4 hours can remove surface adsorbed water and prevent bubbles from being generated during high-temperature processing.
[0055] (2) Weigh out PC resin, ABS resin, toughening agent, compatibilizer, antioxidant and other additives according to the proportion, put them into a high-speed mixer, mix at 300-500 r / min for 2-3 min, then add core-shell flame retardant, mix at 800-1000 r / min for 4-6 min to obtain a mixture; in this step, first mix the non-flame retardant components at low speed to avoid powder flying, and then mix the flame retardant at high speed to use shear force to make the flame retardant evenly dispersed.
[0056] (3) Add the mixture to a twin-screw extruder, control the barrel temperature to 230-280℃ and the screw speed to 350-450r / min, and cool and pelletize after extrusion to obtain the product. In this step, the barrel temperature of 230-280℃ is suitable for the melt processing requirements of PC resin and ABS resin, avoiding high temperature causing component degradation or low temperature causing insufficient melting. The screw speed of 350-450r / min provides sufficient shear force to achieve melt blending of each component, so that the core-shell flame retardant and toughening agent are evenly dispersed.
[0057] As a preferred embodiment of the present invention, the barrel temperature distribution of the twin-screw extruder in step (3) is as follows: feeding section 230-250°C, middle section 250-270°C, and die head 270-280°C. More specifically, the lower temperature of the feeding section can prevent the material from melting and adhering to the screw in advance, thus avoiding bridging and blockage, and at the same time achieves preliminary softening to ensure smooth feeding. The middle section is heated to 250-270°C, which can not only completely melt the PC resin, ABS resin and various additives, providing a good melting environment for the uniform dispersion of each component, but also reduce the high-temperature oxidation of components or the destruction of flame retardant structure because it is lower than the thermal degradation threshold of PC resin and ABS resin. The slightly higher temperature of 270-280°C in the die head section can maintain sufficient melt fluidity and avoid excessive changes in extrusion pressure due to excessive melt viscosity.
[0058] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0059] (1) This invention achieves high-efficiency flame retardancy through a core-shell flame retardant. The core-shell structure design avoids the problems of decreased fluidity and material brittleness caused by excessive addition of traditional flame retardants. The outer shell, made of epoxy polysiloxane, reacts chemically with PC resin and ABS resin through epoxy groups, enhancing the interfacial bonding force. At the same time, the organosilicon forms a stable siloxane heat insulation layer during combustion, which synergistically improves the flame retardant performance of the material. The low molecular weight PC in the middle layer enhances the compatibility between the flame retardant and the PC matrix, making the flame retardant uniformly dispersed and avoiding the decrease in flame retardant performance caused by agglomeration. The core layer is nano-SiO2 loaded with sulfonate. By utilizing the gas-phase flame retardant mechanism of sulfonate and the char formation and drip suppression effect of silicon oxide, the flame spread is rapidly suppressed in the early stage of combustion. The core-shell flame retardant can make the alloy easily reach the UL94 V0 flame retardant standard with low addition amount, and effectively reduces the damage of the flame retardant to the mechanical properties of the material.
[0060] This invention fully utilizes the role of ABS resin in reducing melt viscosity by controlling the ABS resin content to 30-40 parts, significantly improving the fluidity of the alloy and enabling its melt flow rate to meet the injection molding requirements of complex thin-walled products, effectively reducing molding cycle and product defects. At the same time, the addition of 0.5-1.0 parts of silicone flow agent further reduces the internal frictional resistance of the melt, resulting in a significant synergistic effect in improving fluidity without having a significant negative impact on other properties of the material.
[0061] This invention employs a toughening system composed of organosilicon toughening agent, MBS, and hydrogenated SBS. This system can enhance interfacial bonding through the reaction of flexible segments and epoxy groups of organosilicon, and can also synergistically absorb impact energy through the elastic network formed by MBS and hydrogenated SBS. In particular, it improves the low-temperature impact resistance without significantly reducing the rigidity of the material. This results in a significant improvement in the impact resistance of the alloy across the entire temperature range. Furthermore, the total amount of toughening agent is reasonably controlled to avoid a decrease in material rigidity and heat resistance caused by excessive rubber phase. Detailed Implementation
[0062] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below.
[0063] Table 1. Sources of raw materials used in the examples and comparative examples.
[0064]
[0065]
[0066] Example 1:
[0067] This embodiment provides a method for preparing an impact-resistant and flame-retardant PC alloy with melt flowability, including the following steps:
[0068] (1) PC resin was dried at 125℃ for 5 hours, and ABS resin was dried at 85℃ for 3.5 hours;
[0069] (2) The toughening agent is compounded by organosilicon toughening agent, MBS and hydrogenated SBS in a mass ratio of 2.5:3.5:1.5; wherein the organosilicon toughening agent is epoxy polysiloxane with an epoxy value of 0.4 eq / 100g, the rubber phase content of MBS is 55wt% and the average particle size is 0.2μm; the hydrogenation degree of hydrogenated SBS is ≥95%, the styrene segment content is 35wt% and the ethylene-butene segment content is 65wt%;
[0070] The compatibilizer is a mixture of ABS-g-MAH and SAN-g-MAH in a 1:1 mass ratio; wherein the maleic anhydride grafting rate of ABS-g-MAH is 1.2 wt% and the maleic anhydride grafting rate of SAN-g-MAH is 1.0 wt%.
[0071] The antioxidant is a mixture of hindered phenolic antioxidant and phosphite antioxidant in a 1:1 mass ratio; wherein the hindered phenolic antioxidant is antioxidant 1010 and the phosphite antioxidant is antioxidant 168.
[0072] Other additives are compounded from silicone flow agent and lubricant in a mass ratio of 1.5:1; wherein the silicone flow agent is polydimethylsiloxane and the lubricant is ethylene bis-stearamide.
[0073] (3) Add 65 parts of PC resin, 35 parts of ABS resin, 6.5 parts of toughening agent, 0.8 parts of compatibilizer, 0.4 parts of antioxidant and 1.2 parts of other additives into a high-speed mixer and mix at 400 r / min for 2.5 min; add 8 parts of core-shell flame retardant and mix at 900 r / min for 5 min to form a uniformly dispersed mixture.
[0074] (4) Temperature distribution of twin-screw extruder: feeding section 240℃, middle section 260℃, die head 275℃, screw speed 400r / min; after extrusion, water cooling and pelletizing are performed to obtain impact-resistant and flame-retardant PC alloy.
[0075] The preparation method of the core-shell flame retardant in step (3) includes:
[0076] S1. Take nano-SiO2 particles and vacuum dry them at 120℃ for 4 hours; take 7 portions of low molecular weight PC powder with a weight average molecular weight of 6500, pass them through a 200-mesh sieve to remove agglomerated particles, and set them aside.
[0077] S2 dispersed the above 4 parts of dried nano-SiO2 in 100 parts of acetone and ultrasonically dispersed at 300W for 30 min to form a uniform suspension; added 0.4 parts of potassium perfluorohexyl sulfonate and stirred at 25℃ for 2 h to allow potassium perfluorohexyl sulfonate to be uniformly adsorbed onto the surface of nano-SiO2 by electrostatic attraction; after vacuum filtration, washed 3 times with acetone to remove free sulfonates, and vacuum dried at 60℃ for 6 h to obtain nano-SiO2 cores loaded with sulfonates. The loading of sulfonates was found to be 7.5% of the weight of nano-SiO2.
[0078] S3. The above-mentioned sulfonate-loaded nano-SiO2 cores were added to a high-speed mixer and preheated at 80°C and 500 r / min for 5 min. Seven parts of low molecular weight PC powder were slowly added, the temperature was raised to 120°C, and the mixture was stirred at 800 r / min for 30 min to melt and coat the core surface, forming a uniform intermediate layer. After cooling to room temperature, the mixture was pulverized and passed through a 100-mesh sieve to obtain composite particles.
[0079] S4 Take 10 parts of the above composite particles and disperse them in 50 parts of toluene; add 9 parts of epoxy polysiloxane and 0.2 parts of dicumyl peroxide, purge with nitrogen for protection, heat to 110℃ and stir for 2 hours to allow epoxy polysiloxane to be grafted onto the surface of the intermediate PC layer via free radicals to form a chemically bonded outer shell layer. After cooling, filter, wash twice with a toluene-ethanol mixture, and vacuum dry at 80℃ for 8 hours to obtain a core-shell flame retardant; wherein, the mass ratio of sulfonate-loaded nano-SiO2, low molecular weight PC and epoxy polysiloxane is 4.3:7:9.
[0080] Example 2:
[0081] This embodiment provides a method for preparing an impact-resistant and flame-retardant PC alloy with melt flowability, including the following steps:
[0082] (1) PC resin was dried at 120℃ for 4 hours, and ABS resin was dried at 85℃ for 3.5 hours;
[0083] (2) The toughening agent is composed of organosilicon toughening agent, MBS and hydrogenated SBS in a mass ratio of 3:4:1; wherein the organosilicon toughening agent is epoxy polysiloxane with an epoxy value of 0.4 eq / 100g, the rubber phase content of MBS is 55wt% and the average particle size is 0.2μm; the hydrogenation degree of hydrogenated SBS is ≥95%, the styrene segment content is 35wt% and the ethylene-butene segment content is 65wt%;
[0084] The compatibilizer is ABS-g-MAH, and the maleic anhydride grafting rate of ABS-g-MAH is 1.2 wt%.
[0085] The antioxidant is a mixture of hindered phenolic antioxidant and phosphite antioxidant in a 1:1 mass ratio; wherein the hindered phenolic antioxidant is antioxidant 1010 and the phosphite antioxidant is antioxidant 168.
[0086] Other additives are compounded from silicone flow agent and lubricant in a mass ratio of 2:1; wherein the silicone flow agent is polydimethylsiloxane and the lubricant is pentaerythritol stearate.
[0087] (3) Add 60 parts of PC resin, 40 parts of ABS resin, 7 parts of toughening agent, 0.5 parts of compatibilizer, 0.5 parts of antioxidant and 1.5 parts of other additives into a high-speed mixer and mix at 400 r / min for 2.5 min; add 9 parts of core-shell flame retardant and mix at 900 r / min for 5 min to form a uniformly dispersed mixture.
[0088] (4) Temperature distribution of twin-screw extruder: feeding section 235℃, middle section 255℃, die head 270℃, screw speed 380r / min; after extrusion, water cooling and pelletizing are performed to obtain impact-resistant and flame-retardant PC alloy.
[0089] The preparation method of the core-shell flame retardant in step (3) includes:
[0090] S1. Take nano-SiO2 particles and vacuum dry them at 120℃ for 4 hours; take 8 portions of low molecular weight PC powder with a weight average molecular weight of 6500, pass them through a 200-mesh sieve to remove agglomerated particles, and set them aside.
[0091] S2 dispersed the above 3 parts of dried nano-SiO2 in 100 parts of acetone and ultrasonically dispersed at 350W for 35 min to form a uniform suspension; added 0.5 parts of sodium perfluorooctane sulfonate and stirred at 35℃ for 1.5 h to allow sodium perfluorooctane sulfonate to be uniformly adsorbed onto the surface of nano-SiO2 by electrostatic attraction; after vacuum filtration, washed 3 times with acetone to remove free sulfonates, and vacuum dried at 75℃ for 5 h to obtain nano-SiO2 cores loaded with sulfonates. The loading of sulfonates was found to be 9% of the weight of nano-SiO2.
[0092] S3 added the above-mentioned sulfonate-loaded nano-SiO2 core to a high-speed mixer and preheated it for 5 min at 90°C and 400 r / min. Then, 8 parts of low molecular weight PC powder were slowly added, the temperature was raised to 110°C, and the mixture was stirred at 800 r / min for 30 min to melt and coat the core surface, forming a uniform intermediate layer. After cooling to room temperature, the mixture was pulverized and passed through a 100-mesh sieve to obtain composite particles.
[0093] S4 Take 10 parts of the above composite particles and disperse them in 50 parts of toluene; add 10 parts of epoxy polysiloxane and 0.15 parts of dicumyl peroxide, purge with nitrogen for protection, heat to 100℃ and stir for 2.5h to allow the epoxy polysiloxane to be grafted onto the surface of the intermediate PC layer via free radicals to form a chemically bonded outer shell layer. After cooling, filter, wash twice with a toluene-ethanol mixture, and vacuum dry at 70℃ for 9h to obtain the core-shell flame retardant.
[0094] Example 3:
[0095] This embodiment provides a method for preparing an impact-resistant and flame-retardant PC alloy with melt flowability, including the following steps:
[0096] (1) PC resin was dried at 125℃ for 5 hours, and ABS resin was dried at 85℃ for 3.5 hours;
[0097] (2) The toughening agent is composed of organosilicon toughening agent, MBS and hydrogenated SBS in a mass ratio of 2:3:1; wherein the organosilicon toughening agent is epoxy polysiloxane with an epoxy value of 0.4 eq / 100g, the rubber phase content of MBS is 55wt% and the average particle size is 0.2μm; the hydrogenation degree of hydrogenated SBS is ≥95%, the styrene segment content is 35wt% and the ethylene-butene segment content is 65wt%;
[0098] The compatibilizer is a compound of SAN-g-GMA and ABS-g-MAH in a mass ratio of 1:1; wherein the maleic anhydride grafting rate of ABS-g-MAH is 1.2wt% and the epoxy value of SAN-g-GMA is 0.3eq / 100g.
[0099] The antioxidant is a mixture of hindered phenolic antioxidant and phosphite antioxidant in a 1:1 mass ratio; wherein the hindered phenolic antioxidant is antioxidant 1010 and the phosphite antioxidant is antioxidant 168.
[0100] Other additives are compounded from silicone flow agent and lubricant in a mass ratio of 1.5:1; wherein the silicone flow agent is polydimethylsiloxane and the lubricant is ethylene bis-stearamide.
[0101] (3) Add 68 parts of PC resin, 32 parts of ABS resin, 5.5 parts of toughening agent, 1.0 part of compatibilizer, 0.3 parts of antioxidant and 1.0 parts of other additives into a high-speed mixer and mix at 400 r / min for 2.5 min; add 7 parts of core-shell flame retardant and mix at 900 r / min for 5 min to form a uniformly dispersed mixture.
[0102] (4) Temperature distribution of twin-screw extruder: feeding section 245℃, middle section 265℃, die head 280℃, screw speed 400r / min; after extrusion, water cooling and pelletizing are performed to obtain impact-resistant and flame-retardant PC alloy.
[0103] The preparation method of the core-shell flame retardant in step (3) includes:
[0104] S1. Take nano-SiO2 particles and vacuum dry them at 120℃ for 4 hours; take 7 portions of low molecular weight PC powder with a weight average molecular weight of 6500, pass them through a 200-mesh sieve to remove agglomerated particles, and set them aside.
[0105] S2 dispersed the above 4 parts of dried nano-SiO2 in 100 parts of acetone and ultrasonically dispersed at 280W for 35 min to form a uniform suspension; added 0.32 parts of potassium perfluorobutyl sulfonate and potassium perfluorohexyl sulfonate in a mass ratio of 1:1 and stirred at 28℃ for 1.2 h to allow potassium perfluorobutyl sulfonate and potassium perfluorohexyl sulfonate to be uniformly adsorbed on the surface of nano-SiO2 by electrostatic attraction; after vacuum filtration, washed 3 times with acetone to remove free sulfonates, and vacuum dried at 62℃ for 5 h to obtain nano-SiO2 cores loaded with sulfonates. The loading of sulfonates was found to be 7% of the weight of nano-SiO2.
[0106] S3 added the above-mentioned sulfonate-loaded nano-SiO2 core to a high-speed mixer and preheated it at 82°C and 550 r / min for 5 min; slowly added 7 parts of low molecular weight PC powder, heated to 122°C, and stirred at 820 r / min for 30 min to melt and coat the core surface, forming a uniform intermediate layer. After cooling to room temperature, it was pulverized and passed through a 100-mesh sieve to obtain composite particles.
[0107] S4 Take 10 parts of the above composite particles and disperse them in 52 parts of toluene; add 10 parts of epoxy polysiloxane and 0.21 parts of dicumyl peroxide, purge with nitrogen for protection, heat to 100℃ and stir for 2.5h to allow the epoxy polysiloxane to be grafted onto the surface of the intermediate PC layer via free radicals to form a chemically bonded outer shell layer. After cooling, filter, wash twice with a toluene-ethanol mixture, and vacuum dry at 70℃ for 9h to obtain the core-shell flame retardant.
[0108] Comparative Example 1:
[0109] The core-shell flame retardant prepared in Comparative Example 1 differs from the core-shell flame retardant prepared in Example 1 in that it does not contain low molecular weight PC powder as a middle layer.
[0110] Comparative Example 2:
[0111] The core-shell flame retardant prepared in Comparative Example 2 differs from the core-shell flame retardant prepared in Example 1 in that PE is used instead of low molecular weight PC as the intermediate layer material.
[0112] Comparative Example 3:
[0113] The core-shell flame retardant prepared in Comparative Example 3 differs from the core-shell flame retardant prepared in Example 1 in that the nano-SiO2 is not loaded with sulfonate.
[0114] Comparative Example 4:
[0115] Unlike Example 1, the flame retardant in this comparative example was prepared by directly adding the above-mentioned sulfonate-loaded nano-SiO2, low molecular weight PC, and epoxy polysiloxane to a high-speed mixer without layering or coating: stirring at 80°C and 800 r / min for 30 min, and only through mechanical mixing to make the three substances physically contact each other to form a mixed powder; after cooling, passing through a 100-mesh sieve to obtain a non-core-shell flame retardant.
[0116] The PC / ABS granules prepared in the examples and comparative examples were injection molded into specimens and subjected to the following tests: flame retardant performance was tested according to UL94 standard, flexural performance was tested according to GB / T9341-2000, impact performance was tested according to GB / T1843-1996, and melt flow rate was tested according to GB / T3682-2000.
[0117] Based on the above tests, the data in Tables 2 and 3 are obtained:
[0118] Table 2. Test results of flame retardant performance of the examples and comparative examples.
[0119]
[0120] Table 3 shows the test results of bending performance, impact performance, and melt flow rate for the examples and comparative examples.
[0121]
[0122]
[0123] As shown in Tables 2 and 3, in terms of flame retardant performance, Examples 1-3 all achieved the UL94V-0 flame retardant standard under a 1.5mm thin-walled condition, and possessed excellent characteristics such as rapid self-extinguishing upon removal from the flame, no dripping, and low smoke release. This is due to the synergistic flame retardant mechanism of the core-shell structure flame retardant used in this invention, which forms both gaseous and condensed phases. The sulfonate loaded in the core of the core-shell flame retardant can efficiently release fluorine-containing free radicals, capturing H· and OH· in the combustion chain reaction and inhibiting gaseous combustion. The low molecular weight PC in the intermediate layer has a similar molecular structure to the PC matrix, and improves the dispersion stability of the flame retardant through chain segment entanglement. The outer shell epoxy polysiloxane can not only form chemical bonds with the hydroxyl groups of PC and the acrylonitrile groups of ABS to strengthen the interfacial bonding and prevent the flame retardant from detaching, but also form a dense SiO2-based ceramic film through oxidative cross-linking in the early stage of combustion, blocking the transfer of oxygen and heat. In contrast, due to the lack of a low molecular weight PC intermediate layer, replacement of intermediate layer materials, lack of sulfonate loading, or damage to the core-shell structure, the flame retardant synergistic mechanism fails, and the flame retardant level drops to V-1, V-2 or even HB level, accompanied by defects such as dripping and long self-extinguishing time.
[0124] In terms of mechanical properties and processing fluidity, the flexural strength, flexural modulus, cantilever beam notched impact strength, and melt flow rate of Examples 1-3 are significantly higher than those of the comparative examples. The reasons are as follows: First, the toughening agent is a compound of silicone toughening agent, MBS, and hydrogenated SBS in a specific ratio. The silicone toughening agent reacts with the epoxy group of the flame retardant shell to strengthen the interfacial bonding, the MBS rubber phase absorbs the impact energy at room temperature, and the hydrogenated SBS makes up for the shortcomings of low-temperature toughening, thus constructing a full-temperature-range elastic network. Second, the compatibilizer is a compound of ABS-g-MAH, SAN-g-MAH, and SAN-g-GMA. Through esterification or ring-opening reaction between the polar groups and the hydroxyl groups at the PC end, the separation of the PC and ABS phases is eliminated, and the interfacial bonding strength is improved. Third, among the other additives, the silicone flow agent and lubricant synergistically regulate the melt viscosity, ensuring processing fluidity while avoiding the migration of the release agent.
[0125] In the comparative examples, Comparative Example 1 lacked a low molecular weight PC interlayer, directly weakening the chain segment entanglement effect, causing a sharp increase in interfacial tension, decreased dispersibility, and hindering melt flow. Comparative Example 2 replaced the interlayer with PE, but PE has poor compatibility with PC / ABS, failing to form an effective interfacial bond, and phase separation easily occurs in the melt, further deteriorating the flow properties. Comparative Example 3 lacked sulfonate, resulting in uneven flame retardant particle density, which easily settles and agglomerates during processing, disrupting interfacial force transmission and increasing melt resistance. Comparative Example 4 disrupted the core-shell structure and switched to physical mixing, directly exposing and agglomerating the flame retardant. Not only did the interfacial bond completely fail, but the agglomerated particles also significantly hindered melt flow, ultimately leading to a significant deterioration in various properties.
[0126] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. An impact-resistant and flame-retardant PC alloy with melt flowability, characterized in that, By mass, it includes the following components: 60-70 parts of PC resin; 30-40 parts of ABS resin; 6-10 parts of core-shell flame retardant; 5-8 parts toughening agent; Compatibilizer 0.5~1.0 parts; Antioxidant 0.3~0.5 parts; Other adjuvants: 1.0 to 1.5 parts; The core-shell flame retardant consists of nano-SiO2 loaded with sulfonate, low molecular weight PC, and epoxy polysiloxane from the inside out. The low molecular weight PC has a weight-average molecular weight of 5000-8000, and the epoxy value of the epoxy polysiloxane is 0.3-0.5 eq / 100g. The toughening agent is prepared by mixing organosilicon toughening agent, MBS and hydrogenated SBS in a mass ratio of 2~3:3~4:1~2.
2. The impact-resistant and flame-retardant PC alloy with melt flowability as described in claim 1, characterized in that, The PC resin has a weight-average molecular weight of 20,000 to 25,000 and a melt index of 8 to 15 g / 10 min at 300°C and 1.2 kg.
3. The impact-resistant and flame-retardant PC alloy with melt flowability as described in claim 1, characterized in that, The ABS resin contains 22-25% acrylonitrile and ≤28% butadiene, and has a melt index of 15-30 g / 10 min at 220℃ / 10 kg.
4. The impact-resistant and flame-retardant PC alloy with melt flowability as described in claim 1, characterized in that, In the core-shell flame retardant, the mass ratio of the sulfonate-loaded nano-SiO2, the low molecular weight PC, and the epoxy-based polysiloxane is 3~5:6~8:8~10; The nano-SiO2 has an average particle size of 50-100 nm, a surface hydroxyl content of ≥1.5 mmol / g, and a sulfonate loading of 5-10 wt% on the nano-SiO2.
5. The impact-resistant and flame-retardant PC alloy with melt flowability as described in claim 4, characterized in that, The preparation method of the core-shell flame retardant includes: S1. Vacuum-dried nano-SiO2 is prepared for later use; low molecular weight PC is passed through a 200-mesh sieve to remove agglomerated particles and then prepared for later use. S2. Nano-SiO2 was ultrasonically dispersed in acetone, sulfonate was added and stirred at 25~35℃ for 1.5~2.5h, filtered, washed and vacuum dried to obtain nano-SiO2 cores loaded with sulfonate. S3 preheats the sulfonate-loaded nano-SiO2 cores at 70~90℃ and 400~600r / min for 4~6min, adds low molecular weight PC and heats to 110~130℃, stirs at 700~900r / min for 25~35min, cools and pulverizes through a 100-mesh sieve to obtain composite particles. S4. The composite particles are dispersed in toluene, epoxy-based polysiloxane and dicumyl peroxide are added, and the mixture is reacted at 100-120°C for 1.5-2.5 h under nitrogen protection. After washing, the mixture is vacuum dried to obtain a core-shell flame retardant.
6. The impact-resistant and flame-retardant PC alloy with melt flowability as described in claim 1, characterized in that, In the toughening agent, the organosilicon toughening agent is an epoxy polysiloxane, the rubber phase content of the MBS is 50~60wt%, and the average particle size is 0.1~0.3μm; the hydrogenation degree of the hydrogenated SBS is ≥95%, the styrene segment content is 30~40wt%, and the ethylene-butene segment content is 60~70wt%.
7. The impact-resistant and flame-retardant PC alloy with melt flowability as described in claim 1, characterized in that, The compatibilizer is one or a mixture of two or more of ABS-g-MAH, SAN-g-MAH, and SAN-g-GMA.
8. The impact-resistant and flame-retardant PC alloy with melt flowability as described in claim 1, characterized in that, The antioxidant is a compound of hindered phenolic antioxidants and phosphite antioxidants in a mass ratio of 1:
1. The other additives include silicone flow agents and lubricants, with a mass ratio of 1 to 2:
1. The lubricant is ethylene bis-stearamide or pentaerythritol stearate.
9. A method for preparing an impact-resistant and flame-retardant PC alloy with melt flowability as described in any one of claims 1 to 8, characterized in that, Includes the following steps: (1) Dry the PC resin at 120~130℃ for 4~6h and the ABS resin at 80~90℃ for 3~4h; (2) Weigh PC resin, ABS resin, toughening agent, compatibilizer, antioxidant and other additives according to the proportion, put them into a high-speed mixer, mix at 300~500r / min for 2~3min, then add core-shell flame retardant, mix at 800~1000r / min for 4~6min to obtain the mixture. (3) Add the mixture to a twin-screw extruder, control the barrel temperature to 230~280℃ and the screw speed to 350~450r / min, and then cool and pelletize it after extrusion.
10. The method for preparing the impact-resistant and flame-retardant PC alloy with melt flowability as described in claim 9, characterized in that, In step (3), the barrel temperature distribution of the twin-screw extruder is as follows: 230~250℃ in the feeding section, 250~270℃ in the middle section, and 270~280℃ in the die head.
Citation Information
Cited By
Insulating material composition of high-voltage cable as well as preparation method and application of insulating material composition
CN121406044A